A Manipulative Field Experiment to Evaluate the Impact of Discarded Plastic Bags on Shallow Vegetated Benthic Communities - Torn, Kaire; Martin, Georg; Paalme, Tiina; Reisalu, Greta (Frontiers in Marine Science, 2022)
Coastal regions are biologically active areas with significant ecological and socioeconomic values. These regions are increasingly being affected by marine litter. The impact of macro-sized marine litter on biomass and net primary production of hard and soft bottom communities was investigated by using a manipulative field experiment. Plastic bags were used to mimic the disturbance caused by litter to benthic vegetation and fauna. The experiment was carried out on a soft substrate community dominated by sago pondweed Stuckenia pectinata (L.) Boerner and bladder wrack Fucus vesiculosus L. as a foundation species of a hard substrate. A rapid negative impact of the plastic bag cover on vegetation biomass of soft-bottom community was detected, while the impact on the biomass of hard bottom vegetation was non-significant. Plastic bag cover substantially reduced the net production rates of hard substrate species Fucus and the biomass of associated zoobenthos. The difference in net production rates of Stuckenia with and without plastic cover was negligible.